2021
DOI: 10.3389/fnut.2021.672925
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Lactulose as a Prebiotic for Improved Gut Health and Enhanced Mineral Absorption

Abstract: Although medium and high doses of lactulose are used routinely for the treatment of constipation and hepatic encephalopathy, respectively, a wealth of evidence demonstrates that, at low doses, lactulose can also be used as a prebiotic to stimulate the growth of health-promoting bacteria in the gastrointestinal tract. Indeed, multiple preclinical and clinical studies have shown that low doses of lactulose enhance the proliferation of health-promoting gut bacteria (e.g., Bifidobacterium and Lactobacillus spp.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 85 publications
0
20
0
2
Order By: Relevance
“…Based on the prebiotics and osmotic laxative properties, lactulose has been used as a laxative in the treatment of constipation for over 50 years [ 31 ]. This study demonstrated for the first time that lactulose restored the impaired composition and function of gastrointestinal bacteria, in a colitis-associated tumor mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the prebiotics and osmotic laxative properties, lactulose has been used as a laxative in the treatment of constipation for over 50 years [ 31 ]. This study demonstrated for the first time that lactulose restored the impaired composition and function of gastrointestinal bacteria, in a colitis-associated tumor mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, oral supplementation of lactulose (20 gr/kg per 6 weeks) inhibits osteoclastogenesis, reduces bone resorption, and prevents ovariectomy-induced bone loss in mice [ 66 ], while increasing calcium and magnesium absorption in both men and postmenopausal women [ 67 , 68 ].…”
Section: Effects Of Dietary Supplements On the Gut Microbiota And Bon...mentioning
confidence: 99%
“…Впровадження інтенсивних технологій виробництва продукції птахівництва, в т. ч. бройлерного, передбачають застосування різноманітних, екологічно нешкідливих нутріцевтиків, серед яких вітаміни, пробіотики, пребіотики, макро-і мікроелементи тощо (Berri, 2015;Baştürk et al, 2016;Podolyan, 2017;Şanlier et al, 2017;Kasyanenko et al, 2018;Rahimi et al, 2019;Lyasota & Kolodka, 2020;Karadag et al, 2020;Skvortsova, 2020;Konopelko & Lyasota, 2021;Areq Yahya, 2021;Karakan et al, 2021;Ciftciler & Ciftciler, 2021;Kaur et al, 2021;Fabiano et al, 2021;Sanlier & Kocabas, 2021).…”
Section: вступunclassified